Pete the Cat : the first Thanksgiving - Dean, Kim, 1969-; Dean, James, 1957- (New York, NY : Harperfestival, an imprint of HarperCollinsPublishers, 2013)
Pete the Cat participates in a school play about the first Thanksgiving. He makes new friends and learns a lot about what it was like to be a Pilgrim and live off the land, as well as to be thankful for everything. Lift the flaps to see what other adventures and facts came about during the play.
Cover title.
"A lift-the-flap book"--Cover.
Ages 4-8.
Keywords: Cats -- Juvenile fiction; Thanksgiving Day -- Juvenile fiction; Pilgrims and pilgrimages -- Juvenile fiction; Indians of North America -- Juvenile fiction; Lift-the-flap books